The Implementation of the Project-Based Learning Model to Improve Elementary School Students’ Learning Interest in Visual Arts - Awaluddin Muin; Yasmin Justitianalubis (PT. Lontara Digitech Indonesia, 2025)
This study aims to describe the implementation of the Project-Based Learning model in improving students’ learning interest in visual arts among sixth-grade students at SD Inpres 4/82 Pacing. This research used Classroom Action Research with a descriptive qualitative approach. The subjects of this study were 11 sixth-grade students, consisting of 5 male students and 6 female students. The study was conducted in two cycles, and each cycle consisted of planning, action, observation, and reflection stages. Data were collected through teacher activity observation sheets, student activity observation sheets, and student learning interest questionnaires. The data were analyzed using descriptive qualitative analysis through data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Project-Based Learning model improved students’ learning interest in visual arts. Teacher activity increased from 72.22% in Cycle I to 85.25% in Cycle II, while student activity increased from 70.08% in Cycle I to 84.42% in Cycle II. Students’ learning interest also improved, as shown by the decrease in the number of students in the low category and the increase in students in the high and very high categories. These findings indicate that Project-Based Learning can create a more active, creative, collaborative, and meaningful learning process. Therefore, the Project-Based Learning model can be used as an alternative strategy to improve students’ learning interest in visual arts at the elementary school level.